Occurrence conditions of the reverse rotation of rockfall and its influence on the restitution coefficient - Ji, Zhong-Min; Wang, Ting-Hui; Wu, Fa-Quan; Wang, Dong-Po; Li, Zhen-Hua (Frontiers in Earth Science, 2023)
When rockfall occurs along dense rock slopes, the rotation direction of rockfall is not always downhill. Specifically, the rockfall may obtain a reverse rotation speed (RRS) after impact under certain conditions, the effect of which on the restitution coefficient (RC) cannot be ignored.According to the statistical results of the reverse rotation (RR) phenomena of blocks obtained from previous experiments, the occurrence of RR is correlated to the block shape, incident angle, and contact attitude. In this study, considering a typically shaped cubic block, the critical condition for the RR is preliminarily deduced. Based on the results, the influence of the RRS on the RC for four typically shaped blocks is examined using a customized device. Results show that the tangential RC (R t ) values of each block are not sensitive to the change in the RRS, the distribution is relatively concentrated and the values are high. Moreover, the normal RC (R n ) values are not sensitive to the RRS, and the distribution is relatively discrete. The RRS influences R n ; however, it is difficult to directly establish the relationship between them. To this end, considering the contact attitude and shape of the block, an integral variable, the impact coefficient (I c ), is proposed to determine the influence of RRS on R n . Moreover, the impact-bounce behaviours of the block are categorized and analysed. For the block rebound following a single impact, I c and R n are positively and negatively correlated when the mass centre of the block (MC) is in front and behind the contact point (CP), respectively. For the block rebound following two successive impacts, with the increase in I c , the R n